A Novel Fabrication for Manganese Monoxide/Reduced Graphene Oxide Nanocomposite as High Performance Anode of Lithium Ion Battery. (20th April 2016) - Xia, P.; Lin, H.B.; Tu, W.Q.; Chen, X.Q.; Cai, X.; Zheng, X.W.; Xu, M.Q.; Li, W.S.
Graphical abstract: MnO nanoparticles embedded in 3D graphene network possessing a high specific capacity and exhibiting excellent rate capability. Highlights: MnO/rGO nanocomposite is synthesized and evaluated as anode of lithium ion battery. The nanocomposite consists of MnO nanoparticles embedded in rGO network. The nanocompostie exhibits high capacity and good rate and cycle performance. Abstract: In this paper, we propose a novel fabrication for manganese monoxide and reduced graphene oxide nanocomposite (MnO/rGO), in which microemulsion is introduced to form a 3D architecture consisting of MnO nanoparticles embedded in reduced graphene oxide network. Physical characterizations from SEM, TEM, HRTEM, XPS, Raman, and XRD, indicate that MnO particles of about 230 nm are formed and uniformly embedded in rGO. Charge and discharge tests demonstrate that the resulting MnO/rGO exhibits excellent performances as anode of lithium ion battery, delivering a reversible capacity of as high as 776 mAh g −1  at 1000 mA g −1 after 155 cycles and rate capacity of 306 mAh g −1  at 6000 mA g −1 when it is evaluated in a half cell with lithium as the counter electrode.